2009
DOI: 10.1103/physrevd.80.034005
|View full text |Cite
|
Sign up to set email alerts
|

Bound states of the heavy flavor vector mesons andY(4008)andZ1+(4050)

Abstract: systems are studied dynamically in the one boson exchange model, where π, η, σ, ρ and ω exchanges are taken into account. Ten allowed states with low spin parity are considered. We suggest that the 1 −− , 2 ++ , 0 ++ and 0 −+ B * B * molecules should exist, and the D * D * bound states with the same quantum numbers very likely exist as well. However, the CP exotic (1 −+ , 2 +− ) B * B * and D * D * states may not be bound by the one boson exchange potential. We find that the I = 0 configuration is more deeply … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Ding studied the D * D * interaction and found that the D * D * molecular state with J PC = 1 −− can exist. However, if this D * D * molecular state corresponds to Y(4008), we must explain why Y(4008) is very broad [144]. We also notice an interesting phenomenon in Ref.…”
Section: Y States Directly From the E + E − Annihilationmentioning
confidence: 57%
“…Ding studied the D * D * interaction and found that the D * D * molecular state with J PC = 1 −− can exist. However, if this D * D * molecular state corresponds to Y(4008), we must explain why Y(4008) is very broad [144]. We also notice an interesting phenomenon in Ref.…”
Section: Y States Directly From the E + E − Annihilationmentioning
confidence: 57%
“…[56], a strong attraction in the D * D * with J P = 0 + was found, while in Ref. [57] the interpretation of Z + 1 (4050) as a D * D * molecule was not favored. In any case, it is very difficult to understand a bound molecular state which mass is above the D * D * threshold.…”
Section: Z +mentioning
confidence: 94%
“…[237], Ding studied the D * D * system dynamically in the one boson exchange model, and found the interpretation of the Y(4008) as a D * D * molecule is not favored by its huge width, although it is close to the D * D * threshold. However, in Ref.…”
Section: Other Theoretical Schemes Production and Decay Patternsmentioning
confidence: 99%
“…The proximity of their masses to the thresholds inspired molecular explanations of these structures [196,215,216,202,217,218,219,220,221,222,223,224,225,203,226,200,227,228,229,230,231,232,233,234,235,236,237,238,239]. With the refinement of the meson exchange model, many subtle aspects of this framework were investigated, such as the S-D wave mixing effect [185,197], coupled-channel effect [240,241,242], and recoil correction [243,244].…”
Section: The Meson Exchange Modelmentioning
confidence: 99%